2020
DOI: 10.1080/00365521.2020.1820568
|View full text |Cite
|
Sign up to set email alerts
|

Gender, having a positive FIT and type of hospital are important factors for colonoscopy experience in colorectal cancer screening – findings from the SCREESCO study

Abstract: Objectives: Assessing the experience of screening procedures is crucial for improving the quality and acceptance of colonoscopy in colorectal cancer screening. The aim of the study was to investigate the colonoscopy experience and associated factors among individuals who underwent a colonoscopy in the Screening of Swedish Colons (SCREESCO) study. Methods: Participants in the Screening of Swedish Colons (SCREESCO; n ¼ 7593) randomized clinical trial (colonoscopy vs. faecal immunochemical test (FIT)) were enroll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“… 2 , 20 Possible explanations may be that FIT participation is influenced by traditional gender roles in health, while women's embarrassment and worry for pain are more strongly linked to the invasive characteristics of colonoscopy. 2 , 21 Among the test attendees in the FIT × 2 arm, the proportion of test positives was higher among men than among women; this is probably related to biological factors rather than psychosocial/cultural factors. 5 , 20 …”
Section: Discussionmentioning
confidence: 97%
“… 2 , 20 Possible explanations may be that FIT participation is influenced by traditional gender roles in health, while women's embarrassment and worry for pain are more strongly linked to the invasive characteristics of colonoscopy. 2 , 21 Among the test attendees in the FIT × 2 arm, the proportion of test positives was higher among men than among women; this is probably related to biological factors rather than psychosocial/cultural factors. 5 , 20 …”
Section: Discussionmentioning
confidence: 97%
“…Apart from the risk of complications, a positive FIT with a negative follow-up screening colonoscopy could be associated with emotional distress due to the false positive test-more frequent among women-sometimes persisting for a long time after a negative colonoscopy. 40,41 Other studies, however, have shown an improved quality of life after screening colonoscopy regardless of the colonoscopy findings. 42 For detection of the 28 CRCs in women with FIT 40-79 mg/g of which 15 were stages I and II and 8 were stages III and IV, the estimated costs were 16% higher compared to the cost using gender-equal cut-off levels.…”
Section: Discussionmentioning
confidence: 99%
“…It may be difficult to apply U.S. methods to Japan due to differences in health insurance systems and other factors; however, Japan should consider introducing TCS during screening. Five randomized controlled trials assessing the effects of TCS in colorectal cancer screening on reducing mortality are currently in progress 7–11 . The Akita pop‐colon trial randomly assigned participants to an initial TCS intervention or a non‐intervention group 8 .…”
Section: Expectations and Challenges For Population‐based Colonoscopy...mentioning
confidence: 99%
“…Five randomized controlled trials assessing the effects of TCS in colorectal cancer screening on reducing mortality are currently in progress. [7][8][9][10][11] The Akita pop-colon trial randomly assigned participants to an initial TCS intervention or a non-intervention group. 8 Although the primary endpoint of this study is colorectal cancer death, it is expected to produce valuable findings regarding population-based TCS screening, including differences between groups in colorectal cancer stage, the incidence of complications, and clinicopathological features of the discovered lesions.…”
Section: Expectations and Challenges For Population-based Colonoscopy...mentioning
confidence: 99%